2019
DOI: 10.1016/j.mambio.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The price of being bold? Relationship between personality and endoparasitic infection in a tree squirrel

Abstract: The price of being bold? Relationship betw een personality and endoparasitic infection in a tree squirrel Zeitschrift für Säugetierkunde -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 70 publications
8
34
0
1
Order By: Relevance
“…More explorative birds might forage more within this questing range and closer to the ground and, therefore, increase their encounter rate with ticks. Other research has argued that other parasite burdens than tick burden should increase with body mass instead of exploration (Santicchia et al 2019). Some studies have indeed found that parasite burdens can increase with body mass (Kiffner et al 2011; Kiffner et al 2013; Mysterud et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More explorative birds might forage more within this questing range and closer to the ground and, therefore, increase their encounter rate with ticks. Other research has argued that other parasite burdens than tick burden should increase with body mass instead of exploration (Santicchia et al 2019). Some studies have indeed found that parasite burdens can increase with body mass (Kiffner et al 2011; Kiffner et al 2013; Mysterud et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in natural populations based on capture–mark–recapture of animals can rely on the sampling method itself to obtain measure of individual behaviour and/or personality. Indeed, individual differences in willingness to enter a baited trap (trappability) can be considered as a measure of an animal's propensity for risk‐taking (Bisi et al., 2011; Boon et al., 2008; Boyer et al., 2010; Le Coeur et al., 2015; Montiglio et al., 2012; Réale et al., 2000; Santicchia, Gagnaison, et al., 2018; Santicchia et al., 2019). Reactions to risky situations, excluding any component of novelty which is exclusively related to exploration propensity (Réale et al., 2007), have been identified in literature as a measure of individual boldness (Réale et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, also the number of different traps visited (trap‐diversity) can give insights about an animal's movements in the wild (Boyer et al., 2010; Brehm & Mortelliti, 2018; Santicchia, Gagnaison, et al., 2018; Santicchia et al., 2019; Vanden Broecke et al., 2018). This measure can be both informative of an individual's exploration tendency or its space use (Boyer et al., 2010; Réale et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations